Drosophila Models for Human Diseases (Advances in Experimental Medicine and Biology,, 2018)
Most biological pathways, physical and neurological properties are highly conserved between humans and Drosophila and nearly 75% of human disease-causing genes have a functional homologue in Drosophila. This volume provides recent advances in Drosophila models for various human diseases, with each chapter providing a review of studies involving Drosophila models, as well as detailed protocols commonly used in laboratories. Starting with a review of Drosophila's value as a highly tractable model organism for studying human diseases, subsequent chapters present Drosophila models for specific human diseases. The book provides a useful resource for all scientists who are starting to use the Drosophila model in their studies, and for researchers working in the pharmaceutical industry and using new screening models to develop new medicines for various diseases. .